2011
DOI: 10.1162/comj_a_00057
|View full text |Cite
|
Sign up to set email alerts
|

OMChroma: Compositional Control of Sound Synthesis

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…OMChroma (Agon, Stroppa and Assayag 2000) is a compositional framework for the control of sound synthesis in OpenMusic, based on Marco Stroppa’s Chroma system (Stroppa 2000). This framework provides a set of classes (in terms of object-oriented programming) referring to underlying sound synthesis processes.…”
Section: A Generic Framework For the Control Of Sound Spatialisationmentioning
confidence: 99%
“…OMChroma (Agon, Stroppa and Assayag 2000) is a compositional framework for the control of sound synthesis in OpenMusic, based on Marco Stroppa’s Chroma system (Stroppa 2000). This framework provides a set of classes (in terms of object-oriented programming) referring to underlying sound synthesis processes.…”
Section: A Generic Framework For the Control Of Sound Spatialisationmentioning
confidence: 99%
“…A partir desta ideia, denominamos aqui a estereotopia como o deslocamento espacial de uma mesma nota ou dos parciais de um som entre instrumentos em um ensemble. O próprio Ligeti trabalha esta técnica em suas 10 peças para quinteto de sopros, de 1969, e em seu Concerto para violoncelo e orquestra, de 1966.10 "Psychoacoustic research and practical experience have shown the importance of slight deviations in the synthesis parameters, such as jitter, beatings, and vibrato, to obtain sounds that are perceptually more natural, fused, and musically better" (AGON;BRESSON; STROPPA, 2011, p.67-83).…”
unclassified
“…This idea and the concrete data structures used for the representation of events were inspired by earlier works on the OMChroma system[2].…”
mentioning
confidence: 99%